A Study of Dropout Children of MCD Primary Schools of North District of Delhi - Pal, B.K.; Srivastava, R. K. (THE PRIMARY TEACHER, 2006)
The constitution provides for free and compulsory education for all children up to the age of 14 years. Taking this into account, the study of dropouts at the primary level has been carried out in the 17 M.C.D. Primary Schools randomly selected out of 170 M.C.D. schools falling in the civil lines zone of North District of Delhi. To achieve the purpose, a survey proforma regarding the dropout children was developed and administered in the respective schools of the study area. Efforts were made by the investigators to know the reasons for children leaving school before completing the academic session. This study presents the causes of children dropping out. The findings will help educational planners, administrators, and teacher educators in analysing the reasons and taking some measures